Big Data Analytics Strategies for the Smart Grid - Stimmel, Carol L. (Boca Raton : CRC Press, 2015)
A successful data analytics program is the only way utilities will be able to meet the challenges of a modernized grid that is responsive from an operational perspective and meets the demands of greenhouse gas legislation. This book addresses the needs of applying big data technologies and approaches, including Big Data cybersecurity, to the critical infrastructure that makes up the electrical utility grid. It explores the unique needs of electrical utility grids, including operational technology, IT, storage, processing, and transformation to a usable state that benefits the utility business and electricity consumers--
This is a practical book, to be sure, but it is also a book about hope and positive change. I am quite sincere. The delivery of electricity is deeply rooted in the principle of universal access; when clean, reliable energy is available it contributes to poverty alleviation, improved social conditions, and enhanced economic development. In the developed world, we know this to be true. The digital fabric of our lives is a testimony to the importance of energy security. Across the globe, we have seen the vital contributions that electrification has brought to the development of economies and an enhanced quality of life. Nonetheless, this supreme engineering achievement has languished, and we are deeply challenged. Modern electrification systems are degrading and inefficient in myriad ways, yet the complex and difficult operating conditions of the energy business have been slow to adapt and advance to improve these circumstances. However, with the advent of the information-enabled, two-way grid, we have an opportunity to meet these challenges directly. It is the thesis of this book that through the application of big data analytics and subsequent improvements in situational awareness of the millions of miles of grid across the world, we will be able to integrate renewable energy systems, introduce economic and operating efficiencies, and bring energy services to the over 1 billion people across the world who have no electricity. It is also the view of this work that utilities are confronted with a very difficult charge indeed--to evolve rapidly towards a business standpoint that capitalizes on these key technologies--
section 1. The transformative power of data analytics -- section 2. The benefits of smart grid data analytics -- section 3. Implementing data analytics programs for sustained change.
An Auerbach book.
Includes bibliographical references and index.
Also available in print format.
Keywords: Smart power grids; Big data; Electric power distribution; Electronic books